Affective factors contributing to Southeast Asian and East Asian Eighth Graders' science achievement in TIMSS 2015 - Yoon, Fah Lay; Murugan Rajoo (PEC, 2020)
Trends in International Mathematics and Science Study (TIMSS) is an international comparative study that has been implemented by the International Association for the Evaluation of Educational Achievement (IEA) since 1995. This proposed study is aimed to identify the affective factors contributing to eighth graders' science achievement in TIMSS among Southeast Asian and East Asian countries. The freely-downloadable secondary data were analyzed using IEA's International Database (IDB) Analyzer (version 4.0) for TIMSS, a plug-in for SPSS. TIMSS uses an imputation methodology, involving plausible values, to report student performance. This study found that students' views on engaging teaching in science (BSBGESL) were negatively and significantly contributed to eighth-grade students' science achievement in Thailand, Singapore, Chinese Taipei, and Hong Kong SAR. Students Like Learning Science (BSBGSLS) were positively and significantly contributed to eighth-grade students' science achievement in Malaysia, Singapore, Thailand, Hong Kong SAR, and Chinese Taipei. Students Confident in Science (BSBGSCS) were positively and significantly contributed to eighth-grade students' science achievement in Korea, Japan, Chinese Taipei, Hong Kong, Thailand, and Singapore. Students Value Science (BSBGSVS) was positively and significantly contributed to eighth-grade students' science achievement in Japan, Korea, Thailand, Chinese Taipei, Singapore, and Malaysia. Based on the research findings, policy recommendations were made to the Malaysian Ministry of Education to boost Malaysian eighth graders' science performance in the forthcoming TIMSS studies.